Ayurvedic Herbs in Dentistry: Learn How to Manage Oral Health and Tooth Decay with these Modest Herbs? (Journal of Orofacial Research, 1970)
Herbal medicines have been used for many years. Their history can be rooted from ancient civilization wherein their role as a primary source of medication is evident. Many people are looking for a natural approach for caring for teeth after becoming disillusioned with the side effects of modern methods. Despite the advances in various field of medicine, oral infections and dental caries are still considered as serious public health problems and inflict a major burden to health care services around the world and especially in developing countries. Development of resistance against antibiotics and antiseptics is a growing cause of concern which have limited the preventive measures. Therefore, there is a continuing need to search for new antimicrobial agents. Ayurveda has been used for more than five thousand years and has many applications in improving dental health. Ayurveda gives natural ways to prevent and treat oral disease. In rural India, dental care usually not accessible instantly and even not affordable to them but there are so many ayurvedic remedies which they come across in day to day life. The basic idea is that with the help of this article, people will know about the use of various ayurvedic home remedies for oral health and disease, it will encourage the people to maintain their oral health and prevent them from oral disease.